2017
DOI: 10.22214/ijraset.2017.8276
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis: A Survey

Abstract: Sentiment analysis or opinion mining classifies the human's opinion or reviews into the positive, negative and neutral class which are written in form of text about some topic. Social networking sites such as Twitter, Facebook etc are rich in comments, customer reviews, opinion and sentiments. This paper describes the study of different sentiment analysis methods on different web resources such as review sites, blogs, discussion forums and news. It also gives overview of tools and application area of sentiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Sentiment analysis is a branch of Natural Language Processing (NLP) for analysing public opinion [21]. The sentiment analysis is performed in 2 ways, as shown by F. Z. Xing et al [22].…”
Section: Sentiment Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Sentiment analysis is a branch of Natural Language Processing (NLP) for analysing public opinion [21]. The sentiment analysis is performed in 2 ways, as shown by F. Z. Xing et al [22].…”
Section: Sentiment Analysismentioning
confidence: 99%
“…In the past, several studies have been conducted to test sentiment analysis from various social media and news sources using machine learning algorithms. It has been concluded that the accuracy and efficiency of sentiment analysis using the machine learning approach are better than the Lexicon-based approach [21].…”
Section: Fig 4 Machine Learning-based Sentiment Analysis Processmentioning
confidence: 99%